THREE BOTTOM LINE (3BL) DAN CORPORATE SOCIAL RESPONBILITY (CSR) DALAM PENINGKATAN COMPANY IMAGES - Chintia Margaretha Aprilliana (Akubis : Jurnal Akuntansi dan Bisnis, 2019)
The Three Bottom Line or better known as 3BL, consists of three elements forming the People, Planet, Profit. Every company strives to always be the best and can continue to grow at a time through the company's purpose. Profit is the ultimate goal of a company, but that goal would not be run without the activities that integrate between society and the environment therein. Merging the three then known as the Three Bottom line (3BL). 3BL It can be applied in balance between the elements with other elements through Corporate Social Responsibility (CSR). CSR not only can evidence the company cares about the environment or socio around but if the company is successful in a program that has been planned it can be sure the community will be more familiar with the company is a company which imaged well in other words the success of their Corporate Social Responsibility (CSR) as a step to implement 3BL with a more robust and balanced impact on improving the image of the company itself (improving company images). This article will discuss the influence of the three bottom line is run through the CSR program with an increase in the company's images that are conceptual. Kata Kunci : Three Bottom Line (3BL), Corporate Social Responbility (CSR) and Company Images